Avaliação in vitro e in silico do potencial anti-paracoccidioides brasiliensis de chalconas sintéticas - Pereira, Giuliano da Conceição (2024)
The search for new therapeutic compounds is crucial to enhance the patient's clinical condition and provide treatments with minimal adverse effects. Chalcones, substances obtained from natural or synthetic sources and classified as flavonoids, share a common central structure and have garnered increasing interest due to their broad biological activity, including antitumor, antioxidant, anti-inflammatory, antiviral, antibacterial, and antifungal properties. The fungus species Paracoccidioides brasiliensis causes paracoccidioidomycosis (PCM), a systemic fungal infection with the potential to cause severe sequelae and even lead to death. Current therapeutic strategies for systemic fungal infections are time-consuming, costly, and associated with side effects. A database containing 21 chalcones was created and tested in silico for pharmacokinetic attributes, revealing high lipophilicity, gastrointestinal absorption, and permeabilization of the blood-brain barrier. The chalcones showed low Tanimoto similarity with drugs used for PCM. Prediction of chalcones' activities regarding relevant molecular targets in fungal metabolism, along with molecular docking, highlighted significant interactions, especially with fumarate reductase. In silico results were analyzed, and five compounds were selected for in vitro testing. The selected compounds exhibited moderate antifungal activity with MIC values ranging from 32 to >128 µg/mL, all surpassing the standard amphotericin B. In cytotoxicity assays, the five compounds exhibited reduced IC50 values, indicating high cytotoxicity with different values before and after metabolization. Despite promising characteristics, the study suggests that using chalcones as drugs against PCM requires additional studies with the aim to optimize the structure-activity relationship.